Petrogenesis of Dacites in a Triassic Volcanic Arc in the South China Sea: Constraints From Whole Rock and Mineral Geochemistry - Wei, Wu; Liu, Chuan-Zhou; Mitchell, Ross N.; Yan, Wen (Frontiers in Earth Science, 2022)
Triassic volcanic rocks, including basalts and dacites, were drilled from Meiji Atoll in the South China Sea (SCS), which represents a rifted slice from the active continental margin along the Cathaysia Block. In this study, we present apatite and whole rock geochemistry of Meiji dacites to decipher their petrogenesis. Apatite geochronology yielded U-Pb ages of 204-221 Ma, which are identical to zircon U-Pb ages within uncertainty and thus corroborate the formation of the Meiji volcanic rocks during the Late Triassic. Whole rock major elements suggest that Meiji dacites mainly belong to the high-K calc-alkaline series. They display enriched patterns in light rare earth elements (LREE) and flat patterns in heavy rare earth elements (HREE). They show enrichment in large-ion lithophile elements (LILE) and negative anomalies in Eu, Sr, P, Nb, Ta, and Ti. The dacites have initial 87Sr/86Sr ratios of 0.7094 – 0.7113, εNd(t) values of -5.9 – -5.4 and εHf(t) values of -2.9 – -1.7, whereas the apatite has relatively higher initial 87Sr/86Sr ratios (0.71289–0.71968) and similar εNd(t) (-8.13 – -4.56) values. The dacites have homogeneous Pb isotopes, with initial 206Pb/204Pb of 18.73–18.87, 207Pb/204Pb of 15.75–15.80, and 208Pb/204Pb of 38.97–39.17. Modeling results suggest that Meiji dacites can be generated by <40% partial melting of amphibolites containing ~10% garnet. Therefore, we propose that the Meiji dacites were produced by partial melting of the lower continental crust beneath the South China block, triggered by the underplating of mafic magmas as a response to Paleo-Pacific (Panthalassa) subduction during the Triassic. Meiji Atoll, together with other microblocks in the SCS, were rifted from the South China block and drifted southward due to continental extension and the opening of the SCS.